The transition to sustainable living and practice - Leonard, Liam; Barry, John, 1966- (Emerald, 2009)
"The Transition to Sustainable Living and Practice" provides a series of insights into real alternatives to the current economic malaise, with an examination of key themes such as transition towns, traditional villages, new green financial concepts, the sustainable utopia, co-operative farming, sustainability and activism, ecofeminism, green protectionism, intentional communities and a green philosophy of money.
Keywords: Sustainable living.; Sustainable development.; Sustainability.; Social impact of environmental issues.; Science -- Environmental Science.; Business & Economics -- Environmental Economics.; elektronické knihy; electronic books